Mucosal Cryo-Globulin: Mini-Review - Shnawa, Ibrahim M. S.; Algebory, Naeem R. R. (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Human immunoglobulins are sorted in accordance with heat sensitivity into three forms as; Normoglobulin( Norm-opotent) ,cryoglobulin (Cryo-potent) and Pyroglobulin (Pyro-potent). Cryo-globulins existence in human body is being a subject of two holding themes. The first advocates that they are present only in serum. While the second believed that they are present both in serum and other body fluids including urine. The objective of the present chapter was to present a proof for cryo-globulin existence in urine of pulmonary tuberculus patients from whom serum was positive for cryo-globulins. Thus the authors are of the opinion that cryo-globulin present both at serum and body fluids both in health (Normal concentrations) and chronic intracellular bacterial infectious diseases (Abnormal concentrations).